2019
DOI: 10.1177/1463499618814685
|View full text |Cite
|
Sign up to set email alerts
|

Egalitarianism and resistance: A theoretical proposal for Iron Age Northwestern Iberian archaeology

Abstract: We propose a theory of “egalitarianism” as an active historical factor in contexts which have been traditionally considered structurally hostile to it, such as complex agrarian societies. First, we review thoroughly the main anthropological and sociological contributions to resistance against hierarchization in agrarian social contexts (taking into account peasant studies and a segmentary lineage’s tradition). Specific emphasis is placed on the forms of organizing production. Then we go through the archaeologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although heterarchy has been understood from exclusively egalitarian focuses (cf. Currás Refojos and Sastre 2019), the term, in fact, concerns how power can be managed through collective actions, and it may be consistent with different degrees of inequality (Crumley 1995). Indeed, assemblies and collective decision‐making may coexist with deeply hierarchical societies, as was the case in Scandinavia (Semple and Sanmark 2013).…”
Section: Digging the Foundations: Oppida In Our Timesmentioning
confidence: 99%
“…Although heterarchy has been understood from exclusively egalitarian focuses (cf. Currás Refojos and Sastre 2019), the term, in fact, concerns how power can be managed through collective actions, and it may be consistent with different degrees of inequality (Crumley 1995). Indeed, assemblies and collective decision‐making may coexist with deeply hierarchical societies, as was the case in Scandinavia (Semple and Sanmark 2013).…”
Section: Digging the Foundations: Oppida In Our Timesmentioning
confidence: 99%
“…Although some studies have shown that rotary devices were used for finishing ceramic vessels in some areas in North-West Iberia (Corral, 2008), there is no evidence yet for surplus production and trade in ceramics in the same forms as seen in southern and Central Iberia. The absence of surplus production can be considered as an active strategy to counter the processes of hierarchisation seen in other parts of the Iberian Peninsula (Currás and Sastre, 2019). Nevertheless, given the internal variability of socio-economic structures existing in this region (González Ruibal, 2011), the rejection of wheelthrowing might also correspond to other factors, such as the preference for containers made of wood rather than pottery (Torres-Martínez et al, 2018).…”
Section: Chronologies Of the Spread Of The Potter's Wheelmentioning
confidence: 99%
“…The characterization of the forms of social organization within and among these castros has been one of the most relevant issues under discussion. The assessment of the forms and degrees of inequality, especially towards the end of the period, has been the subject of multiple proposals: while some authors have argued that a trend towards a pronounced social inequality might have existed (García Quintela, 2002;González García et al, 2011;Parcero-Oubiña, 2003Parcero-Oubiña and Criado-Boado, 2013), others rather propose that an egalitarian model, based on the durkhemian elaboration of the model of "segmentary societies", is a better description of the communities in this region across the whole Iron Age and until the Roman conquest (Currás and Sastre, 2019;Fernández-Posse and Sánchez-Palencia, 1998;Sastre, 2008Sastre, , 2002.…”
Section: Introductionmentioning
confidence: 99%